Extraskeletal Osteosarcoma in the Duodenum of a Dog - Rezende Souza, Fernanda; de Morais Avelar, Nathalia; Moreira Lopes, Tamara Cristina; Dantas Cassali, Geovanni; Yumi Ribeiro Nakagaki, Karen (Acta Scientiae Veterinariae, 2023)
Background: Osteosarcoma is the most observed primary bone tumor in dogs, and may affect the appendicular and axial skeletons. In addition, it may be present in extraskeletal form, accounting for only 1% of cases. As shown by few reports in the literature, the involvement of the intestinal region by is rare. The objective of this study was to report the case of a 13-year-old Yorkshire dog, submitted to an exploratory laparotomy for suspected partial intestinal obstruction, diagnosed with extraskeletal osteosarcoma. Case: A 13-year-old dog, Yorkshire Terrier, male, presented clinical signs of gastrointestinal abnormalities. An ultrasound examination was performed and was found a mass in small intestine region with wall and lumen invasion. Then, was realized exploratory laparotomy and detected intestinal obstruction due to a mass with approximately 5.0 x 6.0 x 4.4 cm localized in duodenum. Surgical removal was performed and the sample sent to the veterinary diagnostic laboratory for histopathological examination. The sample had an irregular surface and firm consistency. In addition, when cut, the mass enveloped the intestinal layers and sometimes obstructed the lumen. Then, the sample were processed routinely for histopathology. After that, in microscopy evaluation was detected cell proliferation, affecting all layers of intestine. In detail, cells were elongated with pleomorphism marked and atypical mitosis. In addition, there was production of cartilage and bone matrix. So, sue the absence of others sites, the neoplasm was considered primary of intestine. After that, to evaluate the expression of KI-67 and COX-2 was performed, and the cell proliferation index was 54.0% and the COX-2 expression was moderate in less than 10% of neoplastic cells. After the surgery, the patient was hospitalized for a week and continue the treatment in home. Afterwards, the tutor received the diagnosis, but even though he was instructed on the severity of the case, he chose not to undergo chemotherapy. After three months, the patient presented abdominal fluid and nodules in your liver, suggesting metastasis, but without diagnosis confirmation. The patient died five months after the diagnosis of extraskeletal osteosarcoma. However, no necropsy was realized, impossibility the diagnosis confirm. Discussion: The frequency of extraskeletal osteosarcoma in dogs remains unknown, with the mammary glands being the most affected site. In the present study, osteosarcoma affects the duodenal region and no reports of this neoplasm in the duodenum of dogs have been found in the literature. The clinical sign of dyschezia was important for the tutor to refer the animal to the veterinarian and perform the ultrasound in an attempt to elucidate the case, as the tumor mass is not always palpable. Histopathological examination and immunohistochemistry were necessary for the differential diagnosis and to establish the prognosis, although after the surgery the tutor chose not to perform chemotherapy. Extraskeletal osteosarcoma are usually highly metastatic, mainly affecting the lymph nodes and liver. In this case, the patient presented a liver nodule three months after the tumor removal surgery, but unfortunately, there was no diagnostic confirmation. Such neoplastic type is rarer and more aggressive than appendicular and axial OS, with an average survival of 1 to 3 months. In this case, as a necropsy was not obtained, we cannot attribute the survival time to the disease. The survival rates of osteosarcomas in dogs are few months, but in the present case, although the patient died five months after surgery, the failure to perform a necropsy compromises the attribution of survival time to extraskeletal osteosarcoma. Keywords: canine, neoplasm, histopathology, immunohistochemistry.